2009
DOI: 10.1073/pnas.0904890106
|View full text |Cite
|
Sign up to set email alerts
|

Molecular clock is involved in predictive circadian adjustment of renal function

Abstract: Renal excretion of water and major electrolytes exhibits a significant circadian rhythm. This functional periodicity is believed to result, at least in part, from circadian changes in secretion/reabsorption capacities of the distal nephron and collecting ducts. Here, we studied the molecular mechanisms underlying circadian rhythms in the distal nephron segments, i.e., distal convoluted tubule (DCT) and connecting tubule (CNT) and the cortical collecting duct (CCD). Temporal expression analysis performed on mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
238
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 244 publications
(247 citation statements)
references
References 34 publications
7
238
0
2
Order By: Relevance
“…• 30% increased weight gain on high fat diet [80] • Increased susceptibility to sepsis with LPS or Listeria [22,65] • Greater IL-6, TNF␣ [22] • Lower IL-10 [22] Clock Global • Partial diabetes [160] • Reduced NF-B activation in MEFs and BMDMs. [66,116] Clock 19 Global • Obese and display impaired glucose sensitivity with insulin resistance and reduced islet size [112,113] • Increased plasma triglyceride and glucose levels [85,114] • Increased fibrotic damage in model of pulmonary fibrosis [87] • Impaired anti-oxidant defense [87] Cry1/Cry2 Global • Increased NAD+ and ATP.…”
Section: Bmal1-a Master Regulatormentioning
confidence: 99%
“…• 30% increased weight gain on high fat diet [80] • Increased susceptibility to sepsis with LPS or Listeria [22,65] • Greater IL-6, TNF␣ [22] • Lower IL-10 [22] Clock Global • Partial diabetes [160] • Reduced NF-B activation in MEFs and BMDMs. [66,116] Clock 19 Global • Obese and display impaired glucose sensitivity with insulin resistance and reduced islet size [112,113] • Increased plasma triglyceride and glucose levels [85,114] • Increased fibrotic damage in model of pulmonary fibrosis [87] • Impaired anti-oxidant defense [87] Cry1/Cry2 Global • Increased NAD+ and ATP.…”
Section: Bmal1-a Master Regulatormentioning
confidence: 99%
“…In mice, suppression or decrease of the circadian clock activity via deletion of the circadian transcriptional activators Bmal1, Clock, or Npas2 leads to low BP, whereas its constitutive activation via deletion of the circadian repressors Cry1 and Cry2 results in salt-sensitive hypertension. [1][2][3][4] Wang et al have recently shown that mice simultaneously devoid of three prolineand acidic amino acid-rich basic leucine zipper circadian transcriptional factors Dbp, Hlf, and Tef exhibit a significant reduction in BP. 5 Maintaining BP within the normal range strongly depends on the capacity of the kidney to precisely regulate sodium content in the extracellular space.…”
mentioning
confidence: 99%
“…Interestingly, the overall phenotype of the kidney-specific Bmal1 KO is very similar to that of the global KO of CLOCK 12,14 and that of Per1. 8,13,15 The features of these phenotypes include reduced plasma aldosterone, mild polyuria, altered urinary sodium excretion, and reduced BP.…”
mentioning
confidence: 80%
“…Similar relationships between systolic BP and a J-shaped relationship for diastolic BP have been demonstrated in patients receiving maintenance hemodialysis, as well as in patients with less advanced CKD who do not require dialysis. 12,13 In the absence of aortic valve insufficiency, the pattern of high systolic BP, low diastolic BP, and increased pulse pressure are a marker of vascular stiffness. This has been extensively studied in CKD and ESRD, and it reflects accelerated arteriosclerosis and vascular calcification in progressive renal disease.…”
Section: Nonementioning
confidence: 99%
See 1 more Smart Citation